Transition of Care of Disorders of Sexual Development: A Twist of Two Cases with Ambiguous Genitalia - Marshell Tendean; Nanny Natalia. M Soetedjo; Maya Kusumawati; Ervita Ritonga; Hikmat Permana (PP PERKENI, 2024)
Disorders of sexual development (DSD) is a congenital condition that requires an alteration in the development of chromosomal, gonadal, and anatomical sex is atypical. A report showed most of the patients in the 46XX DSD had congenital adrenal hyperplasia (CAH) at 69.23% followed by unknown under-virilization in the 46XY DSD group at 60.09%. Patient 1 diagnosed as DSD 46XX/non-classic congenital adrenal hyperplasia (NCAH) presented with primary amenorrhea, short stature, over-virilization (Prader 2), and 46XX karyotype. Laboratory examination showed elevated 17-hydroxyprogesterone (17OHP): 166.7 ng/ml (2.83 ng/ml), without salt wasting feature. Patient 2 diagnosed with DSD 46XY/type 2 5α -reductase deficiency (SAD) presented with cryptorchidism, under-masculinization (sinecker stage 3b), and 46XY karyotype. Laboratory examination showed elevated testosterone 613 ng/dL (4.6-38.3 ng/dL), decreased dihydrotestosterone (DHT) 11 ng/dL (>20 ng/dL), and elevated testosterone T/DHT ratio 55.73 (8-16). A deep understanding of pathophysiology, and approach to disease in each stage of life is important and warrants special treatment. Comprehensive multidisciplinary team management (MDT) is warranted in DSD management. Disease prognosis varies among each disorder: early detection, treatment compliance, and continuity of care are important to improve patient outcomes.